Synthetic Activity of Recombinant Whole Cell Biocatalysts Containing 2-Deoxy-D-ribose-5-phosphate Aldolase from Pectobacterium atrosepticum - Fernández Varela, Romina Noelia (2022)
In nature 2-deoxy-D-ribose-5-phosphate aldolase (DERA) catalyses the reversible formation of 2-deoxyribose 5-phosphate from D-glyceraldehyde 3-phosphate and acetaldehyde. In addition, this enzyme can use acetaldehyde as the sole substrate, resulting in a tandem aldol reaction, yielding 2,4,6-trideoxy-D-erythro-hexapyranose, which spontaneously cyclizes. This reaction is very useful for the synthesis of the side chain of statin-type drugs used to decrease cholesterol levels in blood. One of the main challenges in the use of DERA in industrial processes, where high substrate loads are needed to achieve the desired productivity, is its inactivation by high acetaldehyde concentration. In this work, the utility of different variants of Pectobacterium atrosepticum DERA (PaDERA) as whole cell biocatalysts to synthesize 2-deoxyribose 5-phosphate and 2,4,6-trideoxy-D-erythro-hexapyranose was analysed. Under optimized conditions, E. coli BL21 (PaDERA C-His AA C49M) whole cells yields 99 % of both products. Furthermore, this enzyme is able to tolerate 500 mM acetaldehyde in a whole-cell experiment which makes it suitable for industrial applications.